PENGARUH MOTIVASI, KOMPENSASI DAN BUDAYA KAIZEN TERHADAP KINERJA KARYAWAN PT. YAMAHA MUSIC MANUFACTURING ASIA - Indra Permana (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2022)
The purpose of this study was to determine how much the influence of motivation, compensation and kaizen culture had on the performance of PT. Yamaha Manufacturing Asia. The research sample was 98 people at PT. Yamaha Music Manufacturing Asia and data collection techniques using online questionnaires through the Google Form application with random sampling technique. The data analysis technique used multiple linear regression analysis with the help of the SPSS version 26 statistical program. The results of this study;(1) Motivation has a significant effect on employee performance with tcount = 6.177 > ttable 1.661 and the contribution is 0.456, so that H1 is accepted; (2) Compensation has no significant effect on employee performance with tcount = 1.126 < ttable 1.661 and the contribution is 0.067, so that H2 is rejected; (3) Kaizen culture has an effect on employee performance with tcount = 6.164 > ttable 1.661 and the contribution is 0.476, so that H3 is accepted; The conclusion of this study is that the motivation and kaizen culture variables partially have a significant effect on employee performance while the compensation variable partially has no effect on employee performance.